Finding Langston - Cline-Ransome, Lesa (Holiday House, 2019)
After his mother's death in 1946, eleven-year-old Langston and his father leave behind their quiet life in Alabama and move to Chicago. Struggling to fit in and missing his mother, Langston finds refuge at the local library where, unlike his library in Alabama, blacks are just as welcome as whites to use. There he discovers the poetry of Langston Hughes and a secret--he was named after this very poet whose work his mother loved.